2001
DOI: 10.1093/jexbot/52.355.351
|View full text |Cite
|
Sign up to set email alerts
|

In situ and in vitro senescence induced by KCl stress: nutritional imbalance, lipid peroxidation and antioxidant metabolism

Abstract: Sunflower (Helianthus annuus L. cv. SH222) plants and calli were exposed to KCl stress for three weeks. Calli were more tolerant to KCl than plants. KCl stress decreased NO(-)(3), Mn, Fe and B levels in whole plants and P, Ca and Mg in shoots. NO(-)(3), P, Ca, Mg, Mn, and B levels decreased in 100 mM-stressed calli. Chlorophyll content, F:(m) and (F:(m)-F:(0))/F:(m) ratio decreased in stressed leaves, while F:(0) increased only in leaves exposed to severe stress (100 and 150 mM). Membrane permeability and lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 35 publications
3
38
0
1
Order By: Relevance
“…Prevention of lipid peroxidation has been considered as one of the key processes in salinity tolerance of tomato cultivars (Juan et al 2005). Proline, besides its well established role as compatible solute in osmoregulation under stress (Santos et al 2001;Ashraf and Foolad 2007), also plays a significant role in hydroxyl radical scavenging (Alia and Mohanty 1997). Activity of antioxidant defense enzymes was largely induced by AMF in the tomato plants in this work.…”
Section: Antioxidant Defense System Under Salinity and Effect Of Amf mentioning
confidence: 63%
See 2 more Smart Citations
“…Prevention of lipid peroxidation has been considered as one of the key processes in salinity tolerance of tomato cultivars (Juan et al 2005). Proline, besides its well established role as compatible solute in osmoregulation under stress (Santos et al 2001;Ashraf and Foolad 2007), also plays a significant role in hydroxyl radical scavenging (Alia and Mohanty 1997). Activity of antioxidant defense enzymes was largely induced by AMF in the tomato plants in this work.…”
Section: Antioxidant Defense System Under Salinity and Effect Of Amf mentioning
confidence: 63%
“…Like other abiotic stresses, salinity also induces oxidative stress in plants (Santos et al 2001;. Plant cells contain an array of protection mechanisms and repair systems that can minimize the occurrence of oxidative damage caused by reactive oxygen species (ROS) (Creissen and Mullineaux 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once ovules were committed to abort, however, the mRNA levels of three other ROS detoxification enzymes decreased. Santos et al (2001) also reported that moderate stress increased catalase, peroxidase, and SOD activities, while higher KCl concentrations decreased peroxidase and SOD activities.…”
Section: Transport Proteins Maintain Ion Homeostasis and Mobilize Nutmentioning
confidence: 89%
“…Membrane permeability was determined by measuring the relative electrolyte conductivity following the method as described previously (Santos et al 2001), with some modifications. Briefly, leaf samples were washed in deionized water to remove surface-adhered ions.…”
Section: Membrane Permeability Determinationsmentioning
confidence: 99%